State-burst feedback control for fault recovery of input/state asynchronous sequential machines - Yang, Jung Min; Park, Seong Jin; Kwak, Seong Woo (Applied Sciences (Switzerland), 2021)
Static corrective controllers are more efficient than dynamic ones since they consist of only logic elements, whereas their existence conditions are more restrictive. In this paper, we present a static corrective control scheme for fault diagnosis and fault tolerant control of input/state asynchronous sequential machines (ASMs) vulnerable to transient faults. The design flexibility of static controllers is enlarged by virtue of using a diagnoser and state bursts. Necessary and sufficient conditions for the existence of a diagnoser and static fault tolerant controller are presented, and the process of controller synthesis is addressed based on the derived condition. Illustrative examples on practical ASMs are provided to show the applicability of the proposed scheme.
Keywords: Asynchronous sequential machines (ASMs); Diagnoser; Fault tolerant control; State bursts; Static corrective control